Pengaruh Penyuluhan Kesehatan Reproduksi Terhadap Tingkat Pengetahuan Dan Sikap Remaja Tentang Hubungan Seksual Pranikah Di SMAN 1 Sukanagara: The Influence of Reproductive Health Education on the Level of Knowledge and Attitudes of Adolescents Regarding Premarital Sexual Relations at SMAN 1 Sukanagara - Anggraeni, Debi (Dohara POAJ, 2024)
Introduction: Adolescence is a period of transition from childhood to adulthood which is marked by increased curiosity, including curiosity related to sexuality. The purpose of this study was to determine the knowledge and attitudes of adolescents about premarital sexual relations at SMAN 1 Sukangara. This study used an experimental approach (quasi-experimental design). Using a questionnaire instrument and related questions, 170 students of class XI IPS participated in this study, which directly collected data from respondents. Methods: This study used an experimental approach (quasi-experimental design). Using a questionnaire instrument and related questions, 170 students of class XI IPS participated in this study which directly collected data from respondents. Results: The results of this research obtained an overview of the lack of knowledge of students regarding premarital sex and there is a relationship between the influence of reproductive health education at SMAN 1 Sukanagara in 2023 with a p-value of 0,000 OR = 154,979 on Adolescent Awareness of Premarital Sexual Relations. The Effect of Reproductive Health Counseling on Adolescents' Views of Premarital Sexual Relations at SMAN 1 Sukanagara in 2023 and Relationship p-value 0,000 OR= 80,322. which means that after the Reproductive Health Counseling (Variable X) the level of knowledge (Variable Y) and Attitude (Variable Z) increased compared to before the counseling was carried out. Discussion: Counseling about premarital sexual relations needs serious attention so that adolescents' insights about premarital sexual relations will increase and be able to create a better generation.